At the crossroads of old and new paths that invite reading - Cencerrado-Malmierca, Luis-Miguel (Anuario ThinkEPI, 2017)
The paper focuses on the role of public libraries as a place to promote reading. It reflects upon how the changes in the world of books and reading, through the influence of technology, can affect the development of the traditional library function. Also the mediating role of the library in the digital age and the strengthening of training and education as essential library functions are discussed. The argument is supported by conclusions drawn from Territorio Ebook, a research project on the digital readout made in Spain with the library as a dynamic axis.